2008
DOI: 10.1158/1055-9965.epi-08-0406
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors and Risk of Meningioma and Glioma

Abstract: Female sex hormones have previously been suggested as possible risk factors for brain tumors, but published studies have reported conflicting results. We conducted a population-based case-control study of glioma (n = 626) and meningioma (n = 906) cases and randomly selected controls stratified on age and geographic region (n = 1,774) in Denmark, Finland, Norway, Sweden, and the United Kingdom. Unconditional logistic regression was used to estimate odds ratios (OR) for glioma and meningioma in relation to repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 49 publications
6
87
1
1
Order By: Relevance
“…Meningiomas may enlarge during hormonal influx, particularly during pregnancy and in the luteal phase of the menstrual cycle. 2 In line with this, spontaneous regression of meningiomas has been reported after pregnancy. 3 Because meningiomas often express progesterone receptors and, albeit to a lesser extent, estrogen receptors, 4,5 it has been postulated that these hormones may influence the increase in tumor size by increasing blood volume and extracellular and intracellular fluid as well as by increasing proliferation of the tumor tissue.…”
Section: Discussionsupporting
confidence: 54%
“…Meningiomas may enlarge during hormonal influx, particularly during pregnancy and in the luteal phase of the menstrual cycle. 2 In line with this, spontaneous regression of meningiomas has been reported after pregnancy. 3 Because meningiomas often express progesterone receptors and, albeit to a lesser extent, estrogen receptors, 4,5 it has been postulated that these hormones may influence the increase in tumor size by increasing blood volume and extracellular and intracellular fluid as well as by increasing proliferation of the tumor tissue.…”
Section: Discussionsupporting
confidence: 54%
“…This phenomenon has been reported specifically for gliomas [3], although one report from New York State indicated that the protective effect of female sex against glioblastomas (the most common form of adult gliomas) decreased after menopause [28]. That our results with respect to male/female rate ratios did not significantly differ by World Area population suggests that this male/ female difference is biologically based and that an explanation should be sought in genetic differences between males and females, sex hormones, and/or female reproductive factors [28,30]. Our results suggest that within an overall context of elevated male risk, female pre-menopausal sex hormones confer increased risk to females.…”
Section: Discussionmentioning
confidence: 57%
“…Our results suggest that within an overall context of elevated male risk, female pre-menopausal sex hormones confer increased risk to females. While reproductive and hormonal factors have been studied in relation to brain cancer risk, results have been conflicting and a coherent understanding has not emerged [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are several lines of evidence suggesting that progesterone may impact meningioma growth. The use of hormone replacement therapy (HRT) [3,12,26] and oral contraceptives [12,14] have been associated with an increased risk of meningioma. Several case reports have suggested a growth-promoting role of progesterone-agonist treatment on meningiomas [2,5,6,22,25].…”
Section: Discussionmentioning
confidence: 99%